Shekuita o el mal trueno: documental performativo, conflictos ontológicos y descolonización de lo real - Rincón, Juan Carlos Valencia; Hoyos, Paula Andrea Restrepo (Cuadernos de Música, Artes Visuales y Artes Escénicas, 2021)
Este artículo analiza las implicaciones ontológicas y el carácter performativo del documental Shekuita o el mal trueno, lanzado en 2017 por un colectivo de producción audio- visual indígena wiwa en la Sierra Nevada de Santa Marta en Colombia. El documental explora las causas, dudas y consecuencias de un triste incidente ocurrido tres años antes: la caída de un rayo sobre una edificación ceremonial de los wiwas, que causó la muerte a casi una docena de líderes. A partir del contraste entre las explicaciones científicas de la tragedia y las que han investigado las autoridades espirituales de la comunidad desde sus ontologías relacionales, y basándonos en un trabajo de campo cuasietnográfico durante el proceso de filmación, buscamos dar cuenta de un caso específico de descolonización de lo real y de los esfuerzos de una comunidad indígena por la libre expresión y la representación autónoma. Encontramos que este documental abre puertas de forma artística a mundos otros, contados en clave insumisa desde una indigenidad que nos interpela. Concluimos que los wiwas performan un realidad que no necesariamente es la que vivieron, sino una que les permite estratégicamente alcanzar más fácilmente la realidad que quieren recuperar. El artículo intenta contribuir a la visibilización de otras ontologías distintas de la naturalista, a mostrar las autocríticas de esta y a manifestar cómo el audiovisual es un espacio propicio para descolonizar lo real. This paper analyzes the ontological implications and the performative nature of the documentary Shekuita o el mal trueno, released in 2017 by a Wiwa indigenous audiovisual production group in Sierra Nevada de Santa Marta, Colombia. The do-cumentary explores the causes, doubts and consequences of a sad incident that happened three years earlier: a lightning strike on a Wiwas ceremonial building, which killed nearly a dozen leaders. Based on the contrast between the scientific explanations of the tragedy and those that the spiritual authorities of the community have investigated according to their relational ontologies and based on a quasi-eth-nographic fieldwork during the filming process, we seek to account for a specific case of decolonization of reality and of the efforts of an indigenous community for free expression and autonomous representation. We find that this documentary opens doors to other worlds in an artistic way, told in an unsubmissive way by an indigenous community that challenges us. We conclude that the Wiwa perform a reality that is not necessarily the one they lived through, but one that strategically allows them to reach the reality they want to recover more easily. The paper at-tempts to contribute to the visibility of other ontologies other than the naturalistic one, to show self-criticism of it and to show how the audiovisual is a propitious space to decolonize reality.
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Créateur.rice autochtone; _Nettoyé

Transformations and Remembrances in the Digital Game We Sing for Healing - LaPensee, Elizabeth A. (Transmotion, 2017)
Digital games, with their capacity for expression and facilitating experience through code, design, art, and audio, offer spaces for Indigenous creatives to contribute to Gerald Vizenor’s characterization of survivance as an active sense of Native presence. Indigenous digital games can be acts of survivance both in the ways they are created as well as the resulting designs. We Sing for Healing is an experiment in developing an Indigenous digital game during limited Internet access that resulted in a musical choose-your-own adventure text game with design, art, and code by Anishinaabe, Métis, and Irish game developer Elizabeth LaPensée alongside music by Peguis First Nation mix artist Exquisite Ghost. The non-linear gameplay expresses traditional storytelling patterns while enabling players to poetically travel in, through, and around traditional teachings. The design uses listening, choosing, and revisiting to reinforce what is best described as a non-linear loopular journey.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Honour water: Gameplay as a Pathway to Anishinaabeg Water Teachings - LaPensée, Elizabeth (Decolonization: Indigeneity, Education & Society, 2018)
Digital games can uniquely express Indigenous teachings by merging design, code, art, and sound. Inspired by Anishinaabe grandmothers leading ceremonial walks known as Nibi Walks, Honour Water (http://www.honourwater.com/) is a singing game that aims to bring awareness to threats to the waters and offer pathways to healing through song. The game was developed with game company Pinnguaq and welcomes people from all over to sing with good intentions for the waters. The hope is to pass on songs through gameplay that encourages comfort with singing and learning Anishinaabemowin. Songs were gifted by Sharon M. Day and the Oshkii Giizhik Singers. Sharon M. Day, who is Bois Forte Band of Ojibwe and one of the founders of the Indigenous Peoples Task Force, has been a leading voice using singing to revitalize the waters. The Oshkii Giizhik Singers, a community of Anishinaabekwe who gather at Fond du Lac reservation, contribute to the healing for singers, communities, and the waters. Water teachings are infused in art and writing by Anishinaabe and Métis game designer, artist, and writer Elizabeth LaPensée. From development to distribution, Honour Water draws on Indigenous ways of knowing to reinforce Anishinaabeg teachings with hope for healing the water.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SPEAR: a Framework for Indigenous Cultural Games - LaPensee, Elizabeth (ANTARES: Letras e Humanidades, 2020)
Video games, which uniquely interweave design, code, art, and sound, can be an especially robust way to express Indigenous cultures. Such games should involve Indigenous people in meaningful roles throughout design and development from conceptualization to distribution with a focus on building capacity to encourage self-determination for Indigenous game developers. This call to action informs SPEAR (Sovereignty, Positionality, Equity, Advocacy, and Reciprocity), a framework for design and development informed by the Indigenous cultural game Thunderbird Strike.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Recherche-création; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Thunderbird Strike: Survivance in/of an Indie Indigenous Game - LaPensée, Elizabeth (Video Game Art Reader 2.1, 2018)
Thunderbird Strike, a 2D side-scroller developed by Elizabeth LaPensée, allows a player fly from the Tar Sands to the Great Lakes as a thunderbird protecting Turtle Island with searing lightning against the snake that threatens to swallow the lands and waters whole. The game encouraged players to learn about the indigenous culture, reflect on water protection and alternative energy sources, and gain awareness of risks posed by oil pipeline construction for the conveyance of tar sands.Thunderbird Strike was developed through residencies including O k’inādās Residency, The Banff Musicians in Residence Program, and Territ-Aur(i)al Imprints Exchange thanks to the 2016 Artist Fellowship grant from the Arrowhead Regional Arts Council.
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Pédagogie décoloniale; 2-Recherche-création; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Call it a Vision Quest : Machinima in a First Nations context - Lapensée, Elizabeth; Lewis, Jason E. (Understanding Machinima Essays on Filmmaking in Virtual Worlds, 2013)
Article sur les machinimas de l'artiste Skawennati (Kanien'kehá:ka) et du travail du laboratoire d'ABTEC (Aboriginal Territories on cyberspace) à l'Université Concordia.
Keywords: 1-Histoire de l'art; 2-Recherche-création; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À vérifier-Jeu vidéo